The Effectiveness Of Intensive Daily Conversation Toward Students Speaking Skill - Ansar Ansar; Sam Hermansyah; Andi Sadapotto; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
The objective of this research were to find out: 1) To find out whether or not the Effectiveness of Intensive daily conversation toward Student Speaking Skills at the Second Semester FKIP Universitas Muhammadiyah Sidrap. 2) To know whether students’ were interested in using Intensive Daily Conversation to improve the speaking skill at the Second Semester FKIP Universitas Muhammadiyah Sidrap. This research employed quantitavive method with used clusster sampling. The population of this research is the second semester; exactly the second semester of FKIP Muhammadiyah Sidenreng Rappang. The total number of population is 114 students. The samples in this research is from 2A1 consist 37 students. So the total sample of the research is 24 students. The data of the research were collected by using two kinds of instrument, namely speaking test and questionnaire. Speaking test was used to obtain data of the students’ speaking ability and questionnaire was used know the students interest in speaking English through Intensive Daily Conversation. The result of data analysis showed that three was significant difference between the students’ score after they were taught by Intensive Daily Conversation and before they were taught by using Intensive Daily Conversation. It was proved by the mean score of the post-test which was higher than the mean score of pre-test (69.5>32.29). Furthermore, the result of the t-test value (0.0005) was greater than t-table (α = 0.05; df = 11; t-table 1.701) which means that H1 was accepted. Then, the analysis of interest by using Likert Scale indicated that the students were interested to speak English by using Intensive Daily Conversation. Based on data analysis, the research concluded that: (1) the used of Intensive Daily Conversation. Improved students’ speaking ability; (2) the used of Intensive Daily Conversation made the students’ interested in speaking English.